Impact of the COVID-19 Pandemic on Loneliness Among Older Adults - Seifert, Alexander; Hassler, Benedikt (Frontiers in Sociology, 2020)
The COVID-19 pandemic has created a pattern of everyday physical distancing worldwide, particularly for adults aged 65+. Such distancing can evoke subjective feelings of loneliness among older adults, but how this pandemic has influenced that loneliness is not yet known. This study, therefore, explored the association between subjective loneliness and different time phases of the COVID-19 pandemic to explain the pandemic’s impact on loneliness among older adults. The analysis employed a sample of 1,990 community-dwelling older adults aged 65–95 (mean age=72.74 years; 43% female) in Switzerland. Data collection occurred both before and after Switzerland’s first confirmed COVID-19 case. Regression models allowed the researchers to determine the binary and multivariate effects of different pandemic time phases on loneliness. The descriptive analysis revealed that loneliness increased after the Swiss government recommended physical distancing and slightly decreased after the Federal Council decided to ease these measures. According to the multivariate analysis, women, lower-income individuals, individuals living alone, individuals with no children, individuals unsatisfied with their contact with neighbors, and individuals interviewed after the physical distancing recommendations were more likely to report greater loneliness. The results suggest the pandemic has affected older adults’ subjective evaluations of their subjective loneliness, and these findings help illustrate the pandemic’s outcomes.